Introducing field digital data collection systems into seasonal malaria chemoprevention campaigns: opportunities for robust evidence development and national e-health strategies. Issue 3 (16th March 2022) - Balla, Kanda; Malm, Kezia; Njie, Ousman; Hounto Ogouyemi, Aurore; Uhomoibhi, Perpetua; Poku-Awuku, Abena; Tchouatieu, André-Marie; Aikpon, Rock; Bah, Alieu; Kolley, Olimatou; Ogbulafor, Nnenna; Oppong, Samuel; et al.
Abstract : Seasonal malaria chemoprevention (SMC) is a World Health Organization-recommended intervention to protect children under the age of 5 in Africa's Sahel region. While SMC remains highly effective in decreasing malaria cases, implementing countries face several challenges regarding collecting quality data; monitoring coverage and compliance and overcoming delays in campaigns due to late payment to field distributors. To address these challenges, the National Malaria Control Programmes of Benin, The Gambia, Ghana and Nigeria introduced digital data collection (DDC) tools to support their SMC campaigns. To facilitate cross-country learning, this paper investigates the impact of using DDCs in SMC campaigns by comparing country responses. Country experience suggests that in comparison to paper-based data collection systems, using DDC tools help to overcome data quality and operational challenges; cloud-based features also made data more accessible. Thus, scaling up DDC tools and linking them with routine national health management systems could help generate robust evidence for malaria policy development and programming. Of note, evidence from Benin showed that using digital tools reduced the time to pay staff and volunteers by 5 weeks. In Benin's experience, DDC also offered cost benefits (1.5 times cheaper) versus the use of paper-based tools. The authors note that no application offers greater benefits than the other—countries will select a technology that best suits their needs. Several applications are currently being used and newer ones are also being developed. Another option is to develop in-house applications that can be adjusted to local health programmes. Cost-effectiveness studies to inform on whether DDCs offer cost advantages would be beneficial. More studies on DDC are needed from SMC-implementing countries to identify additional benefits and drawbacks of digital applications. These will similarly help national malaria policy and programming efforts.